The Compression of Wet Snow - Colbeck,S C; Shaw,K A; Lemieux,G (1978)
The compressibility of wet snow is described in terms of pressure melting and nonlinear viscous deformation at grain contacts. The results of experiments with different salinities and liquid water contents are compared with computed densities. The decreasing compressibility of wet snow with increasing salinity and decreasing liquid content is quantified and explained. Simultaneous particle growth and the doubly charged layer at phase boundaries are included in the model. The results show that the density of wet snow increases approximately as a power of time but is highly dependent on the stress, initial particle size, liquid water content, and ionic impurity content of the snow. (Author)